From InstaCulture to Islamic Ethics: Cultural Hybridization and Halloween Celebrations in Pakistani Society - Waheed, Saima; Ahmad, Mohd. Khairie; Bhatti, Zafar Iqbal (Journal of Islamic Thought and Civilization, 2025)
The current study aimed to explore how Halloween, a Western cultural celebration, is represented on Instagram. Furthermore, the study identified how Pakistani youth engage with or resist such content in light of their religious values. Data was collected in Lahore from 16 participants across four categories: youth, young professionals, parents/educators, and religious scholars. Guided by Agenda-setting and Uses and Gratifications Theories (UGT), the analysis identified six themes. These included representation of Halloween on Instagram, cultural influence via social media, media engagement and user motivation, content creation and sharing behaviour, negotiation between faith and trends, and cultural hybridization and identity. The findings revealed that Instagram frames Halloween as a visually-appealing and secular lifestyle trend, contributing to its normalization in Muslim digital spaces. Youth often interact with such content for entertainment and social belonging. On the other hand, others adopt selective exposure strategies to align with Islamic values. Parents and educators emphasize cultural preservation and moral safeguarding, whereas religious scholars caution against Westernization and the erosion of religious identity. Participants navigated these tensions by reframing their engagement as cultural rather than religious. The study concluded that Pakistani youth are not passive consumers of global media but active negotiators of cultural and religious boundaries. By blending digital trends with faith-based values, they construct hybrid identities that merge Instagram culture with Islamic ethics. This study offered empirical evidence on how Pakistani youth selectively adapt Western cultural trends within an Islamic ethical framework. Additionally, the study contributed to discussions on digital literacy, cultural sensitivity, and the negotiation of global media.